Laboratory Assessment of Epoxy Asphalt Mixture Incorporating Tire Rubber Waste - Shatha S. Hasan; Rasha H. Abd Al-Ameer; Haider A. Hassani (Wasit Journal of Engineering Sciences)
The use of epoxy asphalt in road paving is one of the promising solutions for long-life road pavements in service with minimal maintenance. However, the high cost still stands as an obstacle to the widespread use of this high-performance material. The use of tire rubber waste (TRW) is one of the solutions in order to reduce costs, improve the environment, and improve the performance of epoxy asphalt mixtures, in addition to alleviating the brittle behaviour that epoxy asphalt tends to. This study proposes to add TRW in improving epoxy asphalt produced in local laboratories by using phenol Novolac resin as an epoxy curing agent of the epoxy base inside asphalt binder to produce and evaluate improved epoxy asphalt. The percentage of epoxy base used was 25% of the asphalt binder mixed with a 1:1 ratio of epoxy to Novolac using potassium hydroxide (KOH) as a catalyst. Whereas the proportions of added TRW were (1%, 2%, and 3%) of the total mixture weight by using the dry mixing method. The results showed, at its best values at 2% of TRW, that there was an increase in Marshall stability by 10%, and Marshall flow remained within specification limits with a decrease in the value of air voids at the highest bulk density, and a slight decrease in indirect tensile strength by 2%, with remaining excellent resistance to moisture sensitivity at 94%, and improvement in resistance to permanent deformation (rutting) by 14%. This indicates an improvement in the improved epoxy asphalt mixtures by the addition of TRW compared to the reference epoxy asphalt mixtures.